Micro/Nanophotonic Devices in Europe - Sirleto, Luigi; Righini, Giancarlo C. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint contains the articles accepted for publication in the Special Issue of Micromachines (MDPI) on 'Micro/Nanophotonic Devices in Europe'. It aims at presenting an overview, limited but still representative, of the research in the field of photonics being carried out by European groups (often in collaboration with colleagues abroad). The reprint includes, among others, a review paper on photonic devices fabricated by Germanium implantation and two review articles illustrating the fundamentals of non-linear photonic phenomena and devices, and their main applications.